PENGARUH TRAGAKAN SEBAGAI PENGIKAT TERHADAP SIFAT FISIK TABLET HISAP EKSTRAK JAHE (Zingiber officinalle Roxb.) - Wintari Taurina; Yandi Syukri; Asih Triastuti (Majalah Obat Tradisional, 2013)
Ginger (Zingiber Officinale Roxb.) is a traditional plants usually used to relieve pain, rheumatism, and neutralize poison. The aim of this study was to get the optimum concentration of tragacanth as a binding agent in ginger lozenges formulation. The components from ginger were extracted using percolation with ethanol 70% and then evaporated using rotary evaporator. Lozenges were made in three formulas ; formula 1 (5%), 2 (7,5%), 3 (10%) of tragacanth using wet granulation method. Granules and tablets were tested for its physical properties, and analyzed using Pearson correlation. The result showed that, all of three formulas were good, comply with a regulation of physical properties and soluble time in the mouth. Variation of tragacanth concentration affected physical properties of tablets. It showed that the greater concentration of tragacanth, the larger the hardness and the longer the soluble time of tablets. The formula (tragacanth 10% b/v) gave an optimum physical properties and soluble time of tablets, with weight variety deviation 0,98%, hardness 10,18 kg, friability 0.11% and soluble time 11.50 minutes. The three formulas were received by respondens with prerequirement of improving sweetness, repairing form and the color of tablets.